Atherosclerosis and lymph // risk factors - Božidar Kocmur (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Is there a disease in the human population that has been present since the beginning of the human race, and which has not yet discovered its cause or mechanism of origin? Unfortunately, there is atherosclerosis, a disease that causes the greatest number of unnatural deaths in the world. Atherosclerosis is not the primary disease, as much as the entire life-long degenerative process of thickening and damage to large and medium-sized arteries of the body, related to age.